Rebranding of corporate identity, Wet World Shah Alam / Siti Fatimah Mahat - Mahat, Siti Fatimah (Faculty of Art and Design, 2013)
This academic writing is about rebrand corporate identity for Wet World Shah Alam. Wetworld Water Park Shah Alam is the place for get an exciting water attraction . Based on the website virtualmalaysia.com,it was officially opened in February 1996. Wet World Shah Alam is the place that faces the scenic Taman Tasik Shah Alam. It was the perfect family outing destination and was constructed to be child-friendly and user safe. However, if compared between Wet World Water Park with other water theme park such as Sunway Lagoon, it is less known because of brand.